Use of satellite data in the Geosphere-Biosphere Programme - DESAI, PRANAV S.; JAYARAMAN, V.; NAVALGUND, R. R.; RAJARATNAM, P.; SRIDHARAN, R.; SUBBARAYA, B. H. (MAUSAM, 2003)
This review paper attempts to present a few cases of the utilization of satellite remote sensing data in the Geosphere-Biosphere Programme (GBP), mainly confined to Indian studies, as the international field is too wide to be covered in a brief review. In the overall greenhouse gas injection problem, one of the important questions is the extent of carbon fixation in both, terrestrial and marine eco-systems by photosynthesis. Indian Remote Sensing (IRS) satellite based sensor called ‘Wide Field Sensor (WiFS)’ and Landsat ‘Thematic Mapper (TM)’ have been used, to estimate terrestrial net-primary productivity, closely linked to carbon fixation. Overall forest area and parameters and biodiversity, are also being monitored. The biome-level characterisation of Indian vegetation is being done using WiFS. The carbon pool and cycle of the Indian regions’ terrestrial ecosystems, are also being estimated in a secular study over a number of years, including both carbon dioxide and methane budgeting; the basic data include both in-situ and satellite data sets. Studies on bio-mass burning are being done from WiFS and DMSP OLS data. Similarly, attempts have been initiated to estimate the carbon fixation in marine ecosystems, with special reference to the Arabian Sea and the Bay of Bengal. Productivity/Chlorophyll maps from Indian ‘Ocean Colour Monitor (OCM)’ sensor on Oceansat-1 are the key inputs. As an important component of ‘Land Ocean Interaction at the Coastal Zone’ under GBP, the Chilika lagoon, Orissa, has been extensively studied with in-situ and satellite data from WiFS and OCM, along with LISS, PAN etc. Relevant processes such as transport of carbon, siltation, littoral drift are being studied, besides changes in water quality and productivity related to landuse modifications. Climate modeling to predict future climate, particularly rainfall in response to changes in surface characteristics and atmospheric composition, is a vital study under GBP, in progress. In this context, surface factors like sea surface temperature, deforestation (and its effect on albedo), obtained from in-situ and satellite sources, are being incorporated. Another important surface parameter is ground wetness/soil moisture. Steps are initiated to relate brightness temperature observed by Indian ‘Multi-channel Scanning Microwave Radiometer (MSMR)’ on Oceansat-1 to ground wetness and use this globally. Changes in Himalayan Glaciers are being studied from satellite data. In this, besides WiFS with snow-sensitive channel, stereoscopic PAN is used. Another surface feature of climatic significance is sea-ice at polar regions (Arctic, Antarctic), which too has been mapped seasonally and even, the earlier Nimbus-SMMR based trend extended to present day, from the Indian Oceansat-1 MSMR, in different segments. Another human disturbance occurs in the form of aerosols from industry, vehicles, domestic fuel etc. Indian Oceansat-1 OCM now, and earlier, IRS-P3’s German Payload ‘Multi-spectral Opto-electronic Scanner (MOS)’ are found useful for not only mapping but analysing size/source characteristics of aerosols. These in turn are being incorporated in model calculations. The ocean-atmosphere exchange of latent heat (via evaporation) is being estimated from satellite data such as Oceansat-1 MSMR, which is assisting in diagnostics of models. The radiation budget is an important driver as well as indicator of climate. Radiative fluxes from various satellites/sensors have been compared – e.g. NOAA-AVHRR, INSAT-VHRR, ERBSAT-ERBE. These have been standardized, and utilised in tuning/selecting climate models. Also, special radiative characteristics of the cloud systems in the Indian region have been brought out from such studies.